Stage Lighting: Companies, Teams, Institutions and Professionals in Brazil (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2021)
This article proposes to present the central questions and some partial hypotheses of a research (in progress) of mapping professionals: lighting creators, light designers, light operators and electricians who work in Stage Lighting in Brazil. The objective of the research is to carry out a thorough recognition to understand who the light professionals are for the scene and whether specific training has been obtained in the area. It is expected to contribute to outline the area, to give clues about the role of Stage Lighting professionals in relation to the job market and their professional performance conditions. In addition, it has been guiding and discussing aspects of the training contexts for the performance of the functions of Illuminator, technician or light operator, as well as an understanding of the area and its real demands. In this context, the article will present the research proposal and its development and partial results so far.